Infertility grief and filiation experiences 25 years later: detection of multiple cases from the mixed methods approach - Camps, Núria; Arias-Pujol, Eulàlia; Anguera, M. Teresa (Frontiers in Psychology, 2025)
IntroductionThe diagnosis of infertility generates a significant psychological impact on the couples who experience it. The loss of fertility triggers a psychological mourning process that affects self-esteem and identity. The aim of this study is the follow-up of couples 25 years after conceiving children with artificial insemination of donor semen, to explore from a mixed methods approach the relationship between the mode of elaboration of infertility grief, the communication strategies of the genetic origins of babies and the filiation experience.MethodThe macrostages of the process are QUAL-QUANT-QUAL to integrate qualitative and quantitative elements. The indirect observational methodology has been used, based on in-depth interviews with infertile couples. The observational design is N/F/M: nomothetic (10 couples), incomplete intersessional follow-up (two time points) and incomplete intrasessional follow-up (single in-depth interview), and multidimensional. There are five dimensions proposed based on the theoretical psychoanalytic framework and the answers obtained, which are displayed in sub-dimensions up to the fourth level, and based on each of them a system of categories is developed. The observational instrument is ad hoc, and allows to systematize the transcriptions of the answers, obtaining matrixes of codes (249). After a process of transformation of the data, the quality control of the data is found, and a lag sequential analysis is carried out with the GSEQ5 software, with the aim of detecting regularities in the existence of behavioral patterns.ResultsThe total number of behavior patterns was 55. From the results of the lag sequential analysis five multiple cases have been detected that show that there is a connection between the conducts of the mode of elaboration of infertility grief and the communication of genetic origins and filiation experience.DiscussionQualitative and quantitative elements have been integrated, which is innovative in this substantive area. Likewise, the rigor of a mixed methods approach has facilitated the identification of the deep hidden structure of nuanced aspects in grief coping analysis, which holds relevance for the psychological support of couples undergoing assisted reproduction.